Evaluation of a microvascular anastomotic coupler for end‐to‐side arterial and venous anastomosis for feline renal transplantation. Issue 1 (26th October 2020) - Mickelson, Megan A.; Hardie, Robert J.; Hespel, Adrien‐Maxence; Dreyfus, Jennifer
Abstract: Objective: To describe the technique and determine the feasibility of an end‐to‐side (ETS) anastomosis of the renal vein to vena cava and renal artery to aorta using a microvascular anastomotic coupler (MAC) for feline renal transplantation. Study design: In vivo experimental study. Animals: Six purpose‐bred domestic shorthair cats. Methods: The left kidney was autotransplanted using a MAC for ETS vascular anastomosis. Outcomes included intraoperative hemorrhage from the anastomosis sites, duration of anastomoses, surgical complications, postoperative renal perfusion (including resistive index (RI)) measured by Doppler ultrasonography and computed tomography angiography, and histopathological examination of the left kidney and anastomosis sites (30 days). Results: Anastomosis was successful in all cats, and intraoperative hemorrhage was negligible. Intraoperative renal perfusion was considered excellent. Venous and arterial anastomoses were completed in 11 minutes 20 seconds (range, 6:38‐13:27) and 21 minutes 50 seconds (range, 11:05‐30:24), respectively. Vascular occlusion time was 32 minutes (17:43‐42:03). One cat was euthanized 5 hours postoperatively because of bleeding from a muscular arterial branch of the dorsal aorta causing hemoabdomen. Renal perfusion and RI of the remaining five cats were within normal range (<0.8) and similar to the contralateral kidney at all time points. Endothelialization of the anastomosis was complete with mild‐to‐moderate fibrosis surrounding the MAC in all cats. Conclusion: End‐to‐side anastomosis of the renal vein and artery to the vena cava and aorta, respectively, was consistently achieved in all six cats with the MAC. Clinical significance: The use of the MAC may be considered as an alternative to hand suturing for ETS anastomoses for feline renal transplantation.